Clinical parameters at time of admission as prognostic indicators in cats presented for trauma to an emergency centre in New Zealand: a retrospective analysis. - Fitzgerald WR; Cave NJ; Yozova ID (Massey University, 2022)
OBJECTIVES: The aims of this study were to describe the clinical features of cats presented for trauma in a first-opinion and referral teaching hospital in New Zealand, and to determine the relationship between those features and outcome. METHODS: The electronic medical records of cats presented for trauma to the Massey University Pet Emergency Centre between September 2013 and January 2019 were examined, from which the signalment, clinical parameters and patient outcomes were extracted. Cases were assigned an Animal Trauma Triage (ATT) score and Modified Glasgow Coma Scale (MGCS) score. Variables were selected for inclusion in a logistic regression model to predict survival, and backward elimination was used to find the minimal significant model. RESULTS: In total, 530 cats met the inclusion criteria. The cause of injury was not known in the majority of cases (38.0%). The most common location of injury was the hindlimbs/pelvis/tail (n = 247; 41%), and skin lacerations/abrasions were the most common specific injury. Multivariate analysis revealed altered mentation (odds ratio [OR] 0.31, P = 0.029), hypothermia (rectal temperature <37.8°C [<100.04°F]; OR 0.45, P = 0.015) and an ATT score ⩾5 (OR 0.13, P <0.001) to be statistically significantly associated with mortality. CONCLUSIONS AND RELEVANCE: Altered mentation and hypothermia are easily measurable perfusion parameter abnormalities associated with mortality in cats presenting with trauma. The ATT score appears to be an accurate prognostic indicator in cats presenting with trauma in New Zealand. These results highlight the importance of incorporating a hands-on triage examination in each cat that presents as an emergency after trauma.
(c) The Author/s
Keywords: Animal Trauma Triage score; Hypothermia; Modified Glasgow Coma Scale; level of consciousness; triage; Cats; Animals; Retrospective Studies; Prognosis; New Zealand; Hindlimb; 0707 Veterinary Sciences